Human ophthalmomyiasis caused by Oestrus ovis in Bulgaria: Case Report - Atanasova, Milena Atanasova; Blazhev, Alexander Bozhidarov; Milanova, Elka Tzvetanova; Petrova, Lidiya Plamenova (Frontiers in Ophthalmology, 2025)
Ophthalmomyiasis is an uncommon parasitic infestation of the human eye caused by dipteran larvae, most frequently Oestrus ovis. It is rarely reported in temperate countries such as Bulgaria. We present a case of external ophthalmomyiasis in a 35-year-old urban resident, with no livestock exposure, caused by O. ovis. Larvae were morphologically identified after extraction. Approximately 30 motile larvae were mechanically removed over several days. Microscopy confirmed first-instar O. ovis larvae. Treatment included systemic and topical antibiotics, anti-inflammatory agents, and eye irrigation, resulting in complete recovery. This case of ophthalmomyiasis demonstrated that infestation can occur among urban residents without direct contact with livestock. Early recognition and mechanical removal are essential to prevent ocular damage.